MOTIVASI DAN STRATEGI MANAJEMEN LABA PADA ORGANISASI - Ika Neni Kristanti (P4M STIE Putra Bangsa, 2019)
Earnings management occurs when managers use valuations in financial reporting and in compiling transactions to change financial statements so as to mislead some stakeholders regarding the underlying results that depend on reported accounting figures or to influence contract outcomes that depend on reported accounting figures. The existence of earnings management in a company is inseparable from the various types or underlying motivational factors, while some of the motivations associated with the implementation of earnings management are bonus motivation, political motivation, tax motivation, CEO turnover motivation, IPO motivation. The models used in measuring earnings management include: Healy Model, DeAngelo Model, Jones Model, Industrial Model, Jones Modification Model, Dechow-Dichev Model, Kothari Model and Stubben Model. Keywords : earning management, motivation, measuring models